Effectiveness of Family-Based Health Education in Improving Early Childhood Development Stimulation Practices at PAUD Kasih Bunda Surabaya - Sisilia Indriasari Widianingtyas; Marcellina Rasemi Widayati (STIKES Adi Husada, 2026)
The digital age has transformed parenting patterns, including the increased use of digital devices among young children, which can reduce interaction and developmental stimulation. Families play a crucial role in providing age-appropriate developmental stimulation. Family-based health education is one strategy to enhance parents’ ability to provide developmental stimulation for young children. This study aims to analyze the effectiveness of family-based health education on early childhood developmental stimulation practices in the digital age. This study employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 48 parents of young children at the Kasih Bunda Early Childhood Education Center (PAUD) Surabaya, selected using total sampling. The intervention was delivered through health education on early childhood development stimulation and parenting in the digital age. Data were collected using questionnaires on development stimulation practices before and after the intervention. Data analysis was performed using the Wilcoxon Signed Rank Test with a significance level of p<0.05. The results of the study indicate an increase in developmental stimulation practices following health education, with the proportion of good practices increasing from 29.2% to 83.3%. Statistical analysis revealed a p-value of 0.001 (<0.05). These results indicate that family-based health education can improve parents' capacity to provide developmental stimulation that is considered age-appropriate and promote adaptive parenting techniques in the digital age. Optimal child development outcomes may be supported by integrating family-centered educational programs into early childhood education and community environments.